THE INFLUENCE OF WORK DISCIPLINE, ORGANIZATIONAL CULTURE AND SUPERVISION ON THE PERFORMANCE OF TANJUNG SARI VILLAGE OFFICIAL - Suwandi (Kusuma Negara Business School, 2019)
In the openness and reformation era, the demands and complaints of the people are very easy to become viral and become a negative opinion in the community for leaders in their area. Sometimes the real problem is not like the one that was uploaded by the uploader, but this negative image has become a record of many audiences.Discipline is a feeling of being obedient and obedient to values that are believed to be his responsibility. Discipline is a business effort to instill value or coercion so that the subject has the ability to obey a rule. Supervision is the process of determining performance measures and taking actions that can support the achievement of expected results in accordance with the specified performance. Organizational culture is a system of shared meanings shared by members. Performance is a picture of the level of achievement of the implementation of an activity / program / policy in realizing the goals, objectives, mission, and vision of the organization. From this thought the researcher wants to examine the of Tanjung Sari Cikarang village official whether work discipline, organizational culture and Oversight affect the performance of its Personnel.This study uses a survey method using primary data obtained from questionnaires. Saturated samples in this study were 65 respondence. The data analysis technique uses multiple linear regression.The results showed that: (1) Work discipline has a significant positive effect on employee performance. (2) Organizational Culture has a significant positive effect on employee performance. (3) Oversight has a significant positive effect on the performance of the Tanjung Sari Cikarang village official.